Estimation of IL-17 levels in sera of Iraqi patients with TB and COVID-19 infections with Tocilizumab treatment (Eurasian Medical Research Periodical, 2022)
Background IL-17 has anti-inflammatory activity24. IL-17 cytokine production in peripheral blood after Mycobacterium tuberculosis infection in human25 and also COVID-19 infections. This is the first sight to show the extent of the difference in IL-17 concentration levels produced in response to these infections, either before or after therapy. Methods TB (forty patients) and the other 40 patients of COVID-19 with healthy subjects were included in the present study to estimate IL-17 using an enzyme-linked immunosorbent assay (ELISA). This study is divided by gender and age group factors, as well as measuring the differences in IL-17 concentrations before and after these diseases, with the therapeutic effect of Tocilizumab in this cases according to the outcome and days of hospital after treatment . Results The concentration levels of IL-17 cytokine for tuberculosis and COVID-19 patients according to age group were (234±92.82 and 126.6±15.56 pg/ml, respectively) with a significant statistical difference (p < .05), whereas the evaluated value of IL17 for tuberculosis, COVID-19 patients, and control groups according to gender factor was in females (211.6± 65.61, 141.1±35.33 and 86.68±8.15).The results explained that statistics were different between the study groups before and after treatment according to IL-17 concentration levels.